Pemetaan potensi banjir di Desa Candikuning berbasis Sistem Informasi Geografis (SIG) - Luh Putu Nandha Maha Dewi; Atmaja, Dewa Made; Putra, I Wayan Krisna EKa (Universitas Pendidikan Ganesha, 2024)
This quantitative research aims to identify areas with flood potential in Candikuning Village, Baturiti District, Tabanan Regency. The study was conducted from September 2023 to May 2024. It covers various variables relevant to flood potential, namely rainfall, slope gradient, land use, soil type, and drainage density. To identify flood-prone areas in Candikuning Village, each parameter was scored based on predetermined classifications according to their respective categories. This process involved an in-depth analysis of the collected data. Once these parameters were classified, the next step was to overlay them with the Candikuning Village Administrative Map. In this study, weighted overlays were used to combine data on rainfall, slope gradient, land use, soil type, and drainage density. Each layer of information was weighted based on its importance in contributing to flood potential. The final result of this study is a flood potential map depicting areas in Candikuning Village with varying levels of flood risk. The classifications on this map are divided into five main categories: very low potential, low, medium, high, and very high. This flood potential map is expected to serve as a useful tool for local government and the community in planning flood mitigation measures, as well as in the effective management of natural resources and spatial planning.